2017
DOI: 10.1039/c7ra04605g
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and structural phase transitions of W-doped VO2(R) under pressure

Abstract: The structure transition sequence of W–VO2(R) nanoparticles follows rutile (R) → orthorhombic (CaCl2-type) → monoclinic (Mx) within metallic phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…Zhang et al reported that UFCB‐induced inhibition of CAT activity can be partially attributed to structural changes. UFCB can further affect the activity of CAT by binding to the active center of CAT . The structure of the CAT enzyme in hRBCs was disrupted, resulting in its activity being affected.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al reported that UFCB‐induced inhibition of CAT activity can be partially attributed to structural changes. UFCB can further affect the activity of CAT by binding to the active center of CAT . The structure of the CAT enzyme in hRBCs was disrupted, resulting in its activity being affected.…”
Section: Resultsmentioning
confidence: 99%
“…7, peak (a) and peak (b) are the Rayleigh scattering peak (l em ¼ l ex ) and the secondary-order scattering peak (l em ¼ 2l ex ), respectively. 32 Both the two peaks decreased aer the addition of ARS, indicating that the hydration radius decreased under the exposure of ARS. This result is corresponding to what could be learned from RLS spectra.…”
Section: Effects Of Ars On Secondary Structures Of Catmentioning
confidence: 98%
“…It could be inferred from the gure that ARS slightly unfolded the backbone of ARS, in accordance with the quench of the two peaks. 32 Micro-environment and conformation of CAT was changed, which conrmed the result of synchronous uorescence spectra.…”
Section: Effects Of Ars On Secondary Structures Of Catmentioning
confidence: 99%
See 2 more Smart Citations